VD_FINDINFO Jug / 2023 / 64 vom 19. Juli 2022 - VD Tribunal cantonal (2022)
TENTATIVEDROIT PÉNAL, CONTRAINTEDROIT PÉNAL, PEINE PÉCUNIAIRE, ADMISSION PARTIELLE | 10 CP, 126 al. 2 CP, 22 ad 181 CP, 34 al. 1 CP, 34 al. 2 CP, 42 al. 1 CP, 42 al. 4 CP, 47 al. 1 CP, 47 al. 2 CP